Students’ Perception on Public Speaking Skill: A Case Study in the International Relations Department of Universitas Muhammadiyah Yogyakarta - Patria Handung Jaya; E.J. Syamsy Asriya (Journal of Islamic Studies and Education, 2023)
Idea or creativity is sometimes useless without the ability to tailor it to wider society. Not to mention in this industrial revolution, communication skill is urgently needed by everyone without any exception. This article aims to find out the students’ perception on public speaking skill. There were several students from the International Relations Department who took Public Speaking in their English class as the objects of the research. The result found that students realize that public speaking is important to support their studies. However, they found some obstacles during doing public speaking such as feeling unconfident and the fear of sharing their opinion or as known as Public Speaking Anxiety (PSA). Public speaking is the thing that students can not escape from, even if there are a lot of difficulties they would find. It is expected that after reading this research, students will be more aware of the importance of having public speaking skills.